A fragile watermarking scheme protecting originator's rights for multimedia service - Ting, Grace C. -W.; Goi, Bok-Min; Heng, Swee-Huay (2007)
In ubiquitous environments; users of multimedia service can access to rich multimedia content any time any where, via user-friendly and easy-to-carry handheld, mobile and wearable devices such as mobile phones, PDAs, laptops and even vehicles. Besides the usual requirement of ensuring the integrity and privacy of these contents as they travel from one device to the next, there is also a need for optimal bandwidth use of these devices to ensure the user's comfort in hassle-free access.